Us versus them: race, crime, and gentrification in Chicago neighborhoods - Doering, Jan (Oxford University Press, 2020)
"Crime and gentrification represent hot button issues in racially-diverse neighborhoods. Drawing on three and a half years of ethnographic fieldwork, Us Versus Them provides a detailed analysis of community conflict in Rogers Park and Uptown, two Chicago neighborhoods. The book shows how competing views about neighborhood change divided residents into two political camps, which prioritized either the fight against crime or the fight against gentrification. This division frequently materialized as a type of racial conflict, because anti-gentrification activists and their allies charged that grassroots anti-crime initiatives were, in truth, barely covert racist practices that meant to foster racial displacement and marginalization. Chapter by chapter, the book traces these conflicts in different areas of community life. It examines the strategies of public safety work that residents used to fight crime and how their efforts contributed to gentrification; how anti-gentrification activists resisted criminalization and gentrification; how politicians sought to actively use or downplay community divisions in their electoral campaigns; and how residents of different racial and ethnic backgrounds positioned themselves in these battles"--